Definition of the concept «didactic conditions» in education in pedagogical science - Zhetpisbayeva, B.A.; Benčič, S.; Smagulova, G.T. (KSU Publ., 2017)
There is analysis and theoretical explanation of the concept “didactic conditions” from the standpoint of philosophy category and pedagogical science term initiated in the article. Didactic conditions as an element of didactic system are considered to be the differentiation of pedagogical conditions along with organizational and pedagogical and psychology and pedagogical conditions. Authors have analyzed the variable definitions of the concept “didactic conditions” in education science applied in corresponding context. Generalized nominal classifications and didactic postulates have been additionally taken into consideration. While determining the role and place of the “didactic conditions” element in didactic system the importance of accurate definition of the concept concerning applicable scope is underscored as well as there is set the task of term’s theoretical explanation in relation to foreign language training of specialists.
Педагогика ғылымындағы «дидактикалық шарттар» ұғымының анықтамасы
Определение понятия «дидактические условия» в педагогической науке
Keywords: didactic conditions; pedagogical conditions; didactic system; didactic regularities and principles; procedural components of education process; procedural components of education process; organizational education forms; training process’ aspects; scholastic education; skill and knowledge system; educational environment